The effect of regulating focus tendencies on college students’ sports anomie behavior: the mediating role of autonomous and controlled motivation - Ma, Yimeng; Lu, Laibing; Gu, Bin; Xu, Jinfu; Chen, Mingliang (Frontiers in Psychology, 2025)
IntroductionThis study aimed to investigate the relationship between regulatory focus and sports anomie behavior among university students, examining the potential mediating roles of autonomous and controlled motivation.MethodsA survey was conducted with 2,128 university students using the Long-Term Regulatory Focus Scale, the Behavioral Regulation in Sport Questionnaire, and the College Students’ Sports Anomie Behavior Scale. The study examined the mediating roles of autonomous and controlled motivation in the relationship between regulatory focus and sports anomie behavior through structural equation modeling.Results(1) promotion focus was significantly positively correlated with autonomous motivation, whereas prevention focus was significantly positively correlated with controlled motivation; (2) promotion focus and autonomous motivation were significant negative predictors of sports anomie behavior, while prevention focus and controlled motivation were significant positive predictors; and (3) autonomous motivation partially mediated the relationship between promotion focus and sports anomie behavior, and controlled motivation partially mediated the relationship between prevention focus and sports anomie behavior.DiscussionThese findings highlight the distinct mediating mechanisms through which promotion focus and prevention focus influence sports anomie behavior, emphasizing the important roles of different motivational types in this process.